The additional Protocols TO THE GENEVA CONVENTIONS in Context - Bellal, Annyssa; Casey-Maslen, Stuart (Oxford University Press, 2022)
The Additional Protocols to the 1949 Geneva Conventions remain a landmark in the development of international humanitarian law. The first two Additional Protocols were adopted by states in 1977. These protocols encompass the rules governing the treatment and protection of those in the power of an enemy, as well as the conduct of hostilities. Crucially, they address non-international armed conflicts and wars of national liberation. In 2005, a third additional protocol designating an additional distinctive humanitarian emblem was adopted in controversial circumstances. The Additional Protocols to the Geneva Conventions in Context interprets the key rules and issues of the Additional Protocols and considers their application and implementation over the past forty years. Taking a thematic approach, the book examines subjects including the protection of women, armed non-state actors, relief operations, and prohibited weapons. Each chapter discusses the pertinence of existing laws, the challenges raised by the rules in the Additional Protocols, and what more could be done to better protect civilians. This book also considers whether new technologies, such as offensive cyber operations and autonomous weapons, need new treaty rules to regulate their application in armed conflict.